Assessment of water quality status in UPM-Sebiew-Kemena River System in Bintulu, Sarawak - Nurliyana Yahya
Bintulu has seen tremendous growth in the petrochemical industry, transforming it into an industrial hub for Sarawak. Rapid urbanization and population growth may contribute to the increased level of water pollution. Pollutants may be sourced from anthropogenic activities, which from industrial areas, residential areas, agricultural activities, and markets. This study was conducted to determine and compare the water quality status of UPM, Sebiew, and Kemena river. The sampling was conducted from June to September 2023. In-situ data and water samples were obtained at six sampling stations representing three sampling zones (UPM, Sebiew, Kemena). In-situ data included temperature, pH, turbidity, total dissolved solids (TDS), dissolved oxygen (DO), salinity, and conductivity. Meanwhile, laboratory analysis was conducted to determine the total suspended solids (TSS), ammoniacal nitrogen (NH3-N), chemical oxygen demand (COD), and biochemical oxygen demand (BOD). According to National Water Quality Standard (NWQS), the parameters that categorized under class IIA were temperature, TDS, and conductivity, while turbidity and salinity were in class IIB and class I respectively. According to Water Quality Index (WQI) classification, TSS were classified under class I while COD and BOD were in class II. Value of pH and DO were categorized in class III while NH3-N were in class IV. Only station 1 was classified in class II, while other stations categorized in class III. The subindex for BOD were categorized as slightly polluted, while NH3-N and TSS in those three zones were classified as polluted and clean respectively. All three sampling zones were classified under class III, which was greatly influenced by DO and NH3-N and extensive treatment was required for the purpose of water supply. The presence of pollutants were the contributing factors to the lower Water Quality Index (WQI) obtained. Based on overall data, UPM, Sebiew, and Kemena rivers were classified as slightly polluted. Further study needs to be conducted to observe the long term forecast of these three rivers.